Biodentine used as an apical barrier for the treatment of open apex - Pallavi Srivastava (Journal of Dental Research and Review, 2020)
An immature tooth with pulpal necrosis and periapical pathology imposes a great challenge to the endodontist. Endodontic treatment options for such teeth consist of conventional apexification procedure with and without apical barriers. Biodentine is a new material used for regenerative procedures and advertised as a bioactive dentin substitute. Apexification in one step using an apical plug of Biodentine can be considered a predictable treatment and may be an alternative to mineral trioxide aggregate apexification. This article demonstrates the use of the newer material, Biodentine, which helps in formation of a calcific barrier in a nonvital tooth and helps in the formation of the root apex. This case reports present apexification with the use of biodentine.